A Rare Case of Sclerosing Stromal Tumor of the Ovary Presenting in Pregnancy: A Diagnostic Dilemma on Presentation - Minh Nguyen; Namarig Soumit; Abdul Waheed; Jack Sees; Erum Azhar (Case Reports in Obstetrics and Gynecology)
Sclerosing stromal tumor (SST) is a rare benign neoplasm of the ovary. There are only a few cases of sclerosing stromal tumor of the ovary during pregnancy that have been reported in the literature. The presenting symptoms are nonspecific, including pelvic pain or menstrual irregularities. We describe a case of a young 22-year-old pregnant woman who presented with pelvic pain in the second trimester. On imaging she was found to have a 12 cm left adnexal mass with solid features on MRI. The patient underwent exploratory laparotomy and removal of the mass that was attached to the left ovary via a stalk with preservation of the left ovary. The frozen section diagnosis was “sex cord stromal tumor, favor benign”. The final pathology confirmed the diagnosis of the sclerosing stromal tumor of the ovary where characteristic features of SST including a heterogenous, pseudolobular growth pattern with hypercellular and hypocellular areas were identified along with prominent luteinized stromal cells attributed to pregnancy. In this case report and review of literature, we emphasize consideration of this rare ovarian tumor in the differential diagnosis for a young pregnant woman who presents with pelvic pain.